Analisis Kandungan Klorofil Gandasuli (Hedychium gardnerianum Shephard ex Ker-Gawl) pada Tiga Daerah Perkembangan Daun yang Berbeda - Pratama, Andi Jaya (Prosiding KPSDA, 2015)
The study on chlorophyll concentration of yellow ginger leaf with different area of development has not been conducted thoroughly. Yellow ginger leaf is one of the body plant organ which contains a mountain of fibers which is one of many benefits of this plant. This study aimed to compare the chlorophyll concentration of yellow ginger leaf with different area of development. After extracting leaf chlorophyll using etanol 96%, chlorophyll concentration was measured using spectrometer on Î» 649 and 665 nm. The result showed that the chlorophyll concentration was different among the leaves with different area of development, exactly in the base of leaf contains the most of chlorophyll.